2015
DOI: 10.4103/1947-2714.163646
|View full text |Cite
|
Sign up to set email alerts
|

Double right coronary artery originating from separate ostia: A report of two cases

Abstract: Context:Coronary artery anomalies are uncommon and most are incidental findings. Double right coronary artery (RCA) is a very rare coronary artery anomaly.Case Report:We report two cases of double RCA incidentally found in electrocuted patients. Both cases showed double RCA arising from separate ostia. On microscopy, both right coronaries showed no significant pathology in the first case while in the second case, the posterior RCA showed features of obliterative arteritis.Conclusion:Although double coronary ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…It is generally assumed that coronary artery anomalies are relatively rare, occurring in about 1% of patients. In most cases, they affect the LCA ( 28 , 40 ). However, this is not confirmed by findings from veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally assumed that coronary artery anomalies are relatively rare, occurring in about 1% of patients. In most cases, they affect the LCA ( 28 , 40 ). However, this is not confirmed by findings from veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological variations related to the location of coronary ostia may lead to myocardial ischaemia, infarction, and sudden death. It should be emphasised that the presence of accessory coronary vessels or a single coronary artery (SCA) are recognised as rare anomalies in about 1% of patients ( 15 , 28 , 40 ). Variations associated with the location of coronary ostia were found in 0.3% of cadavers in a necropsy series and in 1.6% of patients undergoing coronary angiography ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study concluded that it is not always easy to differentiate dual RCA from high splitting of PLV branch. In reality it is a split RCA, wrongly labelled as dual RCA [ 6 ]. Another study has shown that during coronary angiography, right anterior oblique (RAO) view can help in differentiating the dual RCA from the large right ventricular artery [ 7 ].…”
Section: Discussionmentioning
confidence: 99%